The Eden-Eisenhower correspondence, 1955-1957 - Eden, Anthony, Earl of Avon, 1897-1977 (University of North Carolina Press, 2005)
The personal correspondence between President Eisenhower and Prime Minister Eden during the time they were simultaneously in office tells of a relationship that began with promise but ended in division. Issues that influenced the Anglo-American relationship - the Soviet Union, nuclear concerns, colonialism, the Middle and Far East - are covered.